The effect of advertisement choice on attention - Nettelhorst, Stephen C.; Brannon, Laura A. (My University, 2012)
The purpose of this study was to assess the effect of advertisement choice on individuals’ subsequent attention towards the advertisement. Participants in this study decided which type of advertisement to watch or they were not given a choice. Results of the study showed that advertisement choice significantly influenced female participants’ subsequent attention towards the advertisement but not males’. This effect suggests that this marketing technique should be used in specific situations to target women predominately. These include marketing products predominately or universally used by females or during shows which are viewed by a large number of females.
Keywords: Advertisement choice; Sex differences; Attention; Selective exposure